Pengaruh Kinerja Keuangan, Economic Value Added dan Market Value Added terhadap Return Saham Perusahaan Manufaktur - Arisky Andrinaldo; Husaini Husaini; Darman Usman; Ronal Aprianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
In investing in capital markets, an investor needs to consider the expected level of return (Return). This study aims to examine whether financial performance (net income, NOPAT, EPS), EVA, and MVA significantly influence stock returns. The object of this research is Manufacturing Companies registered in 2013 to 2017. This study uses secondary data with a purposive sampling method. The data obtained in this study were 52 company samples. Analysis method of this research data is multiple linear regression. The results showed that net income and market value added had a significant effect on stock returns, and earnings per share and economic value added had no significant effect on stock returns. In addition, earnings per share and economic value added have no significant effect on stock returns. Based on the results of this study, signal theory influences information generated through net income and market value added to investors to respond to the signals given in making investment decisions in order to produce the expected stock returns. Future studies are expected to add to the research period and other independent variables that affect stock returns. Keywords: Stock Returns, Net Income, Earning Per Share, Economic Value Added, and Market Value Added